Potensi Herbal Medicine dalam Pencegahan Gangguan Menstruasi dan Sindrom Premenstrual : Kajian Literatur Sistematik - Fransiska Mochtar; Saddam Muhdi; Yessi Rahayu; Ami Amelia (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Menstrual disorders and premenstrual syndrome (PMS) are common gynecological conditions that significantly impact women's quality of life and productivity. Herbal medicine, used both traditionally and supported by scientific evidence, offers a promising preventive approach. This study aims to systematically evaluate the effectiveness of herbal medicine in preventing menstrual disorders and PMS. A systematic literature search was conducted following the PRISMA 2020 guidelines using databases such as PubMed, Scopus, ScienceDirect, and the Cochrane Library for articles published between January 2013 and December 2023. Out of 1,143 articles identified, 26 studies met the inclusion criteria. The most frequently studied herbs included Vitex agnus-castus, Zingiber officinale, Curcuma longa, and Foeniculum vulgare. Several randomized controlled trials reported significant improvements in PMS symptoms and menstrual cycle regulation. These findings support the potential of herbal medicine as an effective preventive strategy; however, further high-quality clinical trials with standardized preparations and long-term follow-up are needed for clinical validation.